UPAYA PEMERINTAH INDONESIA DALAM MENGHADAPI PENGHINDARAN PAJAK OLEH MULTINATIONAL CORPORATIONS (MNCS): STUDI KASUS PAJAK GOOGLE TAHUN 2016-2019 - M. Amris Alfiansa (2021)
This research aims to find out how digital Multinational Corporations (MNCs), especially Google, can avoid taxes in Indonesia. Seeing the high income of Google obtained from the results of its operations in Indonesia. This study also aims to determine the efforts of the Indonesian government in dealing with cases of tax evasion in the period of 2016-2019. This study uses the concepts of digital economy, multinational corporations, and international tax law with the use of qualitative methods (case study) in the analysis process to provide answers in descriptive form regarding facts related to MNCs tax violations that occurred in Indonesia and how the Indonesian government's efforts in dealing with the case. The researcher found that Indonesia made various efforts such as demanding Google to become a permanent establishment, negotiating taxes with Google, exchanging data with United Kingdom, setting tax policies unilaterally, and being committed to supporting global consensus. However, these efforts certainly have obstacles so that this problem cannot be resolved quickly.